Analisis Faktor Perpindahan Tenaga Kerja Dari Sektor Pertanian ke Sektor Industri (Studi Kasus Kecamatan Gondanglegi Kabupaten Malang) - Dailabi, M. Miqdad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The transfer of labor from agriculture to industry also affect workers in the countryside as a whole. The pattern of employment in rural areas is an overview of the absorption patterns tenag work in Indonesia. This happens because most of the population live in rural Indonesia The role of the agricultural sector is still one of the sectors that can create jobs is enormous, although employment growth in this sector has decreased from year to year. Increasing the number of employment in the industrial sector from year to year continues to increase. It takes place in line with the process of industrialization in development.This study aims to determine 1). To determine the factors that influence the transfer of labor from agriculture to industry. 2). To determine the effect of variable land area, level of education, technology, and the level of wages on movement of workers from agriculture to industry.The result is that the factors of land use, education level factors and factors of wage rates are factors that affect the movement of workers from agriculture to industry and the most dominant factor influence on the movement of workers is the educational level where the higher the level of education of farmers the opportunity to relocate to the industrial sector is getting bigger, and their desire to leave the farm even higher because many have the expertise and excellence in fields other than farming experience. Despite the growth of the agricultural sector has always declined, development in the agricultural sector can not be ignored because the majority of Indonesian territory is rural and the need for improvement of employment arrangement so that no labor shortages teerjadi who work in the agricultural sector.Keywords: Displacement of Labor, Agriculture Sector, Industry Sector.